On unified class of γ-spirallike functions of complex order - Seoudy, T. M. (Sarajevo Journal of Mathematics, 2024)
In this paper, we obtain a necessary and sufficient condition for functions to be in an unified class of γ-spirallike functions of complex order. Some of our results generalize previously known results.